TEACHER HOW MUCH IS BETTER? THE DIFFERENTIAL ROLE OF BILINGUAL EDUCATION - Santos David, Ricardo (LINKSCIENCEPLACE, 2026)
The objective of these studies is to show the importance of bilingual education in child development. The methodology is a literature search. The results of this study show that early bilingual education is conducive to cognitive development of children. It has been shown the positive effect of bilingualism on intellectual functioning in relation to monolingualism, since the child has been exposed to a certain amount of bilingual exposure as soon as possible. Early bilingual effect will be greater in bilingual actively started to use more than one language early in life. This hypothesis is in accordance with the voluminous literature addressing the effects of early acquisition in the field of language and literacy development.